A Survey of Dry Processed Corn Particle Size and Fecal Starch in Midwestern U.S. Feedlots - E. F. Schwandt; D. U. Thomson; S. J. Bartle; C. D. Reinhardt (Kansas Agricultural Experiment Station Research Reports, 2017)
Optimizing grain processing practices in cattle feeding operations is critical to reaching maximum feed utilization efficiency. An increased degree of grain processing has consistently shown improved dry matter and starch digestibility; however, it exists with conflicting results on improving performance in finishing cattle. These inconsistencies are likely due to diet composition, such as roughage and co-product level, that could offset the effects of reduced particle size on rate of fermentation thus reducing the risk of digestive dysfunction. Finishing diets are commonly formulated with processed grain to increase utilization of starch and improve animal performance. Processing methods including steam-flaking, grinding, or dry-rolling improve total tract starch digestibility compared with that of whole grain. When dry-rolling corn for finishing cattle, recommendations often suggest that grain be coarsely processed, or cracked to prevent production of an excessive quantity of fine material that could potentially result in an increased rate of fermentation, reduced rumen pH, and digestive disturbances. However, previous research has reported that inclusion of dried distillers grains in finishing diets may influence optimal grain processing method. Grinding corn to a finer particle size when the grain is fed in combination with distillers grains may result in improved total tract starch utilization without causing reduced ruminal pH and digestive disturbances. The objective of this survey was to provide the feedlot industry with an indication of average particle size distribution from current manufacturing practices of dry processed corn, fecal starch content, and co-product and roughage inclusion levels in Midwestern feedlots.
Keywords: dry rolled corn; feedlot; particle size